A jurisprudência do Conselho Administrativo de Recursos Fiscais: análise da interpretação das normas relativas à amortização de ágio dos casos envolvendo empresas-veículo - Rosa, Luiz Eduardo Miranda (2020)
The purpose of this study is to analyze the adequacy of the hermeneutic techniques recently adopted by CARF in its decisions, specifically those regarding the right to the goodwill tax amortization in cases involving conduit companies, to understand their context and assess their validity in light of the Brazilian legal system. In recent years, it has been easy to observe that CARF has consistently issued decisions that are more aligned to the Treasury’s positions, rather than the taxpayer’s. The analysis of such decisions reveals, in many cases, CARF’s paradigm shift concerning the criteria for the tax law interpretation, with the adoption of concepts and institutes that lack legal grounds in our legislative order, such as “substance over form”, “business purpose”, among others, to the detriment of the strict legal interpretation that previously prevailed in the Administrative Court. This phenomenon has been intensifying and shows no signs of mitigation. Nevertheless, one should bear in mind that the Brazilian legal system is highly codified and favors legal certainty. In this context, it is necessary to deeply analyze the rules and criteria that must direct the interpretation of the Brazilian tax legislation in order to assess if this new paradigm, which has been guiding the most recent CARF decisions, is sheltered in our legal system. Hence, a thorough study of the subject is necessary to propose means to harmonize these new trends with the Brazilian legal system, ensuring taxpayers a minimum legal certainty and a mitigation of the risk of being surprised with tax assessments and decisions dissociated from the rules that guide the Brazilian legal system